Fatigue in Multiple Sclerosis: General and Perceived Fatigue Does Not Depend on Corticospinal Tract Dysfunction - Mordillo-Mateos, Laura; Soto-Leon, Vanesa; Torres-Pareja, Marta; Peinado-Palomino, Diego; Mendoza-Laiz, Nuria; Alonso-Bonilla, Carlos; Dileone, Michele; Rotondi, Mario; Aguilar, Juan; Oliviero, Antonio (Frontiers in Neurology, 2019)
Background: Multiple sclerosis (MS) is an autoimmune disorder of the CNS in which inflammation, demyelination and axonal damage of the central nervous system coexist. Fatigue is one of the most disabling symptoms in MS and little is known about the neurophysiological mechanisms involved. Methods: To give more mechanistic insight of fatigue in MS, we studied a cohort of 17 MS patients and a group of 16 age-matched healthy controls. Baseline Fatigue Severity Scales and Fatigue Rating were obtained from both groups to check the level of fatigue and to perform statistical correlations with fatigue-induced neurophysiologic changes. To induce fatigue we used a handgrip task. During the fatiguing task, we evaluated fatigue trait (using a dynamometer) and after the task we evaluated the Borg Rating of Perceived Exertion Scale. Transcranial magnetic stimulation and peripheral electric stimulation were used to assess corticospinal tract and peripheral system functions before and after the task. Results: Clinically significant fatigue and central motor conduction time were greater in patients than in controls, while motor cortex excitability was decreased and maximal handgrip strength reduced in patients. Interestingly, fatigue trait was positively correlated to perceived fatigue in controls but not in patients. Furthermore, in the presence of similar fatigue trait over time, controls showed a significant fatigue-related reduction in motor evoked potential (a putative marker of central fatigue) whereas this effect was not seen in patients. Conclusions: in MS patients the pathogenesis of fatigue seems not driven by the mechanisms directly related to corticospinal function (that characterize fatigue in controls) but seems probably due to other “central abnormalities” upstream to primary motor cortex.